Population-level incidence and outcomes of myocardial infarction with non-obstructive coronary arteries (MINOCA): Insights from the Alberta contemporary acute coronary syndrome patients invasive treatment strategies (COAPT) study. (1st August 2018) - Bainey, Kevin R.; Welsh, Robert C.; Alemayehu, Wendimagegn; Westerhout, Cynthia M.; Traboulsi, Dean; Anderson, Todd; Brass, Neil; Armstrong, Paul W.; Kaul, Padma
Abstract: Background: Myocardial infarction with non-obstructive coronary arteries (MINOCA) is a known clinical conundrum with limited investigation. Using a large population-based cohort, we examined the incidence, demographic profile, use of evidence-based medicines (EBM) and clinical outcomes of MINOCA patients. Methods: Patients hospitalized with a primary diagnosis of MI who underwent coronary angiography between 01/04/2002 and 31/03/2014 in Alberta, Canada, were included in the study. Comparisons were made between patients with MINOCA versus obstructive coronary disease (OCD). The primary composite endpoint was 1-year all-cause death or re-MI. Results: Of 35, 928 patients hospitalized with MI, 2092 (5.8%) had MINOCA. In-hospital mortality rate was 0.8% among MINOCA, and 2.7% among patients with OCD ( p  < 0.0001). At 6 months, cardiovascular EBM rates were significantly lower among MINOCA patients compared to OCD patients. One-year death/re-MI rate was 5.3% in MINOCA and 8.9% in patients with OCD (adjusted hazard ratio (AHR) 0.75, 95% confidence interval (CI) 0.62–0.92, p  < 0.0001). Five-year mortality rates were 10.9% in MINOCA and 16.0% in patients with OCD. Upon further stratification, 770 (36.8%) of MINOCA patients had no angiographic evidence of CAD (i.e. normal angiograms). EBM rates were even lower among these patients. One-year death/re-MI rate among these patients was 3.9% as compared to 6.1% among MINOCA patients with stenosis <50% (AHR 0.68, 95% CI 0.44–1.07, p  = 0.028). Conclusions: The population-level incidence of MINOCA is approximately 5%. Despite their apparently benign anatomic findings, efforts must be made to improve secondary prevention strategies to reduce the burden of long-term adverse outcomes in this population. Highlights: In a large, population-based analysis of MI patients, 5.8% present with MINOCA. One-year death/re-MI rate was 5.3% in MINOCA and 8.9% in patients with OCD. 770 (36.8%) of MINOCA patients had no angiographic evidence of CAD. One-year death/re-MI rate among these patients was still 3.9%. Despite the benign anatomic findings, clinical outcomes in MINOCA are still of concern.